THE USE OF PICTURE ON SOSIOLOGI LEARNING PROSES AT SMAN 1 V KOTO KAMPUNG DALAM KABUPATEN PADANG PARIAMAN - Yestanova, Rilla; Adiyalmon, Adiyalmon; Erningsih, Erningsih (Pendidikan Sosiologi, 2013)
Media is everything that can be used to channel a message from sender to receiver in order to stimulate mind, feeling, attention, and student interest while teaching and learning process. Media picture is one of the media in teaching process because as fasilities to support teacher and student activing in the classroom, media picture have many benefit to the teacher and student in learning process. So, the skill of the teacher is needed to design and use media picture in sosiology learning process. The purpose of this research is to ekpress the us of picture on sosiology Â learning process at SMAN 1 V Koto Kampung Dalam Kabupaten Padang Pariaman.This research is qualitative approach related to descriptive. The informant is purposive sampling related to the teacher that using media picture on sosiology learning and to the student that use media picture. Also, the the informant of this research are 2 teacher and 8 student at SMAN 1 V Koto Kampung Dalam. The method of this research are: 1) interview, 2) observation, 3) documentation. The technique of data analysis related to Miles and Huberman: 1) Data collection, 2) Data reduction, 3) Data display, 4) Conclusion.The result of the research: media picture is benefit to the teacher and student on sociology learning process, for the teacher: 1) Teacher is easy to explain the material, 2) To decrease student boring and enjoy the class. Beside to the student: 1) the material is easy to understand, 2) to motivate the student in teaching and learning process when the teacher use media picture.